Exploring the Diversity of Asbāb al-Wurūd Utilities in Jurisprudential Hadiths - Ananda Prayogi; Fahrur Razi; Alwi Shobri (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
Without knowledge of the asbāb al-wurūd, individuals can easily misunderstand hadiths. Moreover, the specific hadith under consideration serves as a source of Islamic jurisprudence (jurispridential hadith or hadith of fiqh), thereby potentially leading to errors in legal interpretations. To mitigate such occurrences, this article aims to elucidate the concept of asbāb al-wurūd both theoretically and practically in the context of understanding fiqh-related hadiths. This research addresses three key questions: a) the definition and principles of asbāb al-wurūd; b) the significance of hadith in Islamic jurisprudence; and c) the application of asbāb al-wurūd in interpreting fiqh-related hadiths. Through a literature review and qualitative descriptive analysis, data is gathered from diverse reliable sources, including journal articles, traditional texts (turāth), scholarly works, and credible documents. The findings demonstrate that asbāb al-wurūd involves studying the contextual background of hadiths to discern their intended meanings. Furthermore, the application of asbāb al-wurūd in fiqh-related hadiths encompasses six functions: specifying the general, defining the absolute, elaborating on the universal, clarifying abrogated rulings (naskh), providing legal reasoning (taṣrīḥ), and explaining ambiguities (musykil).